PENDIDIKAN SEKS PADA ANAK USIA 4-5 TAHUN DI TAMAN KANAK-KANAK MUJAHIDIN PONTIANAK - Olifia, Nonita; Ali, Muhamad; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research purposed to know how well sex education being told to the kids around 4-5 years old students of Mujahidin 1 Kindergarten, Pontianak. This research applying qualitative approach, with the descriptive method. The subjects in this research are the group of A1, A2, and A3, with the total students of 48 kids consists of 30 boy students and 18 girl students. The technique in data collecting is direct observation, direct communication, and documentary study. The stage in analyzing the data are, search the data, arrange it, classify the important one and finally drawing conclusion in order to make the data developed and evaluated. Conclusions: sex education in children aged 4-5 years in Mujahidin 1 Kindergarten Pontianak, can be categorized well, this is because the material delivered by the teacher in sex learning is adjusted to the theory proposed by nurul chomaria and the material delivered is also in accordance with the level of understanding children aged 4-5 know, besides that the teacher also uses a variety of ways and media, the method used by the teacher is adjusted to the level of achievement of children aged 4-5 years, the media used are also diverse.Keywords : Kids around 4-5 years old, Sex Education